The Shooting - Joyce, Adrien; Nicholson, Jack; Hellman, Monte, 1932-; Perkins, Millie, 1938-; Proteus Films ([United States] : Proteus Films, 1967)
A beautiful woman (Millie Perkins) traveling alone convinces a former bounty hunter (Warren Oates) and a gunman (Hill Hutchins) to escort her on a journey through the Utah desert. Although both do not know the reason for such an odyssey, they will soon suspect that it is about hunting a man, especially when they discover that they are not alone, but that a murderer (Jack Nicholson) follows them. According to the director himself, this film tries to be a metaphor for the short-lived fame of Lee Harry Oswald.--
Jack Nicholson, Millie Perkins, Will Hutchins, Warren Oates, Charles Eastman, B.J. Merholz.
Director of photography, Gregory Sandor ; music, Richard Markowitz.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed June 16, 2022)
Keywords: Bounty hunters -- Drama; Revenge -- Drama; Motion pictures; Western films; Feature films; Fiction films; Streaming video